Astragalus tijuanensis and Astragalus brauntonii var. lativexillum, a new species and a new variety in the genus Astragalus (Fabaceae) from extreme northwestern Baja California, Mexico - Estrada Castillón, Eduardo; Rebman, Jon P.; González, Carlos; Villarreal Quintanilla, José Ángel (Phytotaxa, 2022)
We describe and illustrate Astragalus tijuanensis, morphologically related to Astragalus palmeri, and Astragalus brauntonii var. lativexillum as a new species and a new variety respectively from extreme northwestern Baja California, Mexico. Both new taxa were discovered growing on specialized clay soils in a recently burned chaparral habitat, both taxa are extremely rare and threatened.